Unusual Presentation of Gastric Perforation by Foreign Body: A Case Report - V. S. R. Rao; R. Sarkar; Richard Turner; K. R. Wedgwood (Case Reports in Surgery)
Perforation of the gastrointestinal tract by ingested foreign body is rare. The majority of patients do not recall ingestion of the foreign body, and dietary foreign bodies are most commonly involved. We present an interesting case where the offending foreign body gave rise to a diagnostic dilemma masquerading as a pancreatic mass. A high index of suspicion is indicated especially when dealing with atypical presentation and nonspecific symptoms as highlighted in this case.